Application of the vacuum method to obtain graphite (Texas Journal of Engineering and Technology, 2022)
The article discusses the conceptual requirements for deposition methods widely used in modern microelectronics. The high deposition rate and the atomic energy incident on the substrate during deposition allow these methods to be used to obtain films with various compositions and structures, especially for low temperature epitaxy.